Long‐term response to osimertinib in elderly patients with lung adenocarcinoma harbouring de novo EGFR T790M: a case report and literature review - Sumi, Toshiyuki (Respirol Case Rep, 2021)
Osimertinib is a potent and irreversible epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) that selectively acts on both EGFR‐sensitive and EGFR T790M‐resistant mutations. Patients with pre‐treatment EGFR T790M mutations (de novo EGFR T790M) respond poorly to existing EGFR‐TKIs, whereas osimertinib has positive effects. However, the safety data for first‐line osimertinib treatment in patients aged >75 years are insufficient. We treated two elderly patients with de novo EGFR T790M mutations with osimertinib as the first‐line therapy. We found that the first‐line treatment with osimertinib was safe and resulted in a long‐term response in elderly patients with de novo EGFR T790M‐mutated lung adenocarcinoma.